The Lucerne Toolbox 3: digital health and artificial intelligence to optimise the patient journey in early breast cancer : a multidisciplinary consensus : policy review - Pfob, André; Pinker, Katja; Vaz-Luis, Ines; Di Meglio, Antonio; Cardoso, Maria João; Curigliano, Giuseppe; Gentilini, Oreste Davide; Gruber, Günther; Hauser, Nik; Heil, Jörg; Kaidar-Person, Orit; Knauer, Michael; et al. (The lancet. Oncology, 2025)
The Lucerne Toolbox 3 initiative addresses the pressing need for evidence-based integration of digital health and artificial intelligence (AI) technologies in early breast cancer care. The multidisciplinary consortium identified and prioritised 15 crucial medical knowledge gaps across the patient journey, from diagnosis to treatment and survivorship, using a modified Delphi consensus process with 112 unique members from 27 countries and 16 medical societies, trial groups, and patient organisations. The knowledge gaps include AI-based mammography screening, personalised screening strategies, digital knowledge databases, AI-driven treatment optimisation, and digitally delivered monitoring and supportive care. The consortium developed 13 trial designs in the Population, Intervention, Comparison, and Outcome format to address these gaps, achieving consensus or majority vote in 98% of statements. The recommendations emphasise precision medicine, patient-centred care, and interdisciplinary collaboration to improve outcomes, efficiency, and equity in breast cancer care. By presenting a roadmap for actionable trials, Lucerne Toolbox 3 sets a foundation for advancing digital health in breast cancer care.